Prevalence of Burnout syndrome in health professionals of an onco-hematological pediatric hospital - Aline Bedin Zanatta; Sergio Roberto de Lucca (SciELO, 2015)
OBJECTIVE To identify the prevalence of Burnout Syndrome in medical professionals, nurses and nursing technicians working in an Onco-Hematological Pediatric Hospital in São Paulo. METHOD An exploratory, descriptive study with cross-sectional design and quantitative approach, with a sample of 188 health professionals. Data were collected using two self-report instruments: the Maslach Burnout Inventory (MBI-HSS) which is a biosocial data form, and a non-participant observation guide. RESULTS High depersonalization for nurses (29.8%), low job performance for physicians (27.8%), and of nursing technicians (25.5%). High scores were identified in at least two domains of Burnout in 19.2% of nurses, 16.8% of nursing technicians, and 16.6% of doctors. CONCLUSION Health professionals are highly vulnerable to each of the dimensions of Burnout syndrome - namely emotional exhaustion, alienation, and low job performance/satisfaction- in the hospital work.